PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI SPARE PARTS COPOTAN BORONG - Aswin Saputra; Muh. Ichsan Fachri Azis (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2021)
This study aims to determine the significant effect of service quality on customer satisfaction in spare Parts Copotan Borong. This research uses two approaches, namely the caulitative approach and quantitative approach. The data collection method that is used is this study using survey research that takes samples from one population and uses questionnaires as a basic data collection tool. The analysis method used is descriptive statistical analysis and multiple linear regression analysis. The results showed that: 1) there is a significant influence the quality of service to customer satisfaction in spare Parts Copotan Borong. 2) by 79%, while the remaining 21% is influenced by other independent variables that are not examined in this study include price, discounts, location, and others.